Effect of Y alloying on microstructure and mechanical properties of as-annealed Ti6Al4V alloys - Li-na Jiao; Lu Mao; Bao-hua Duan; Qi-sheng Feng; Guang-yao Chen; Chong-he Li (Journal of Materials Research and Technology)
The Ti6Al4V alloy with Y used as the deoxidizer contains a certain amount of Y. In this study, the effects of Y on the mechanical properties of the Ti6Al4V alloy were investigated. The phase components, compositions, and microstructures of as-annealed samples were examined using X-ray diffraction analysis, scanning electron microscopy, and transmission electron microscopy, respectively. The results revealed that trace elemental Y was uniformly dissolved in the alloys and that excess Y led to the formation of Y2O3, which strengthened the samples. Among the alloys tested, that without Y exhibited the highest yield strength and elongation, whereas that containing 0.4 at% Y exhibited the highest tensile strength, and the elongation was not significantly reduced. In contrast, when the Y content exceeded 0.4 at%, the grain-boundary segregation of Y2O3 was more distinct, and the mechanical properties deteriorated significantly. The deoxidized Ti6Al4V alloy with a residual Y content of 0.072 at% exhibited improvements in the microstructure and mechanical properties compared with the base metal. This study provides valuable insights for enhancing the mechanical properties of Ti6Al4V through Y addition.